General practitioners tackling burden of non-communicable diseases in primary care setting of Nepal: way forward - Dangal, Binod; Kharal, Puspa Mani (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Non-communicable Diseases (NCDs) are the major causes of morbidity and mortality globally. The increasing trends of NCDs and their risk factors such as physical inactivity, tobacco, alcohol use, unhealthy diet, high blood pressure and obesity has put enormous pressure on the fragile and challenged health system of Nepal. General Practitioners (GPs) are leading most of the district level hospitals in Nepal providing holistic primary health care. Primary health care led by GPs offers an effective platform to address NCDs through preventive and curative interventions in Nepal. We discuss some challenges and some strategic solutions to tackle NCD burden via primary care approach in Nepal.